The stability-and-peace accelerator: an overview - Dahl, Hauke; Jacobs-Mata, Inga (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2023)
For the 1.5 billion people living in Fragile and Conflict Affected Settings (FCAs), livelihood challenges and rising food, fertiliser, and input prices are compounded by climate change, unsustainable resource consumption, poor governance, and weak social cohesion . Economic disruptions, such as those caused by COVID-19 and the war in Ukraine, are sparking the risk of food and nutrition crises and poverty and conflict traps. Global hunger, remained relatively unchanged from 2021 to 2022 but is still far above pre-COVID-19- pandemic levels, affecting around 9.2 percent of the world population in 2022 compared with 7.9 percent in 2019. It is estimated that between 691 and 783 million people in the world faced hunger in 2022. Considering the midrange (about 735 million), 122 million more people faced hunger in 2022 than in 2019, before the global pandemic. Given the compounding challenges, the purpose of the Stability-and-Peace Accelerator programme is to identify and enable the scaling of high-impact, high potential innovations which promote the resilience of Food, Land and Water Systems (FLWS) in Fragile and Conflict Affected Settings (FCAs) in migrant and host communities — thus enabling food and nutrition security, climate resilience, social cohesion, and sustainability in emergency and humanitarian settings. In order to achieve this purpose, the programme will source high potential innovations, award grants to said innovations, promote capacity building of innovations with a local footprint, and harness the immense technical expertise of CGIAR scientists to support the innovations. Through a partnership with the WFP Innovation Accelerator, the programme can leverage cutting-edge research, data-driven solutions, and further best practices in food systems innovation, food security, sustainable resource management and climate security. This collaboration enables a refined comprehension of the challenges faced in fragile settings, allowing for context-specific interventions that can effectively address issues like food insecurity, land degradation, and water scarcity. By accessing the specialised knowledge within the Fragility Conflict and Migration initiative and additional CGIAR actors, the partnership can ensure the likelihood of success for scaling scientifically validated, climatesmart solutions in the sector, as well as to provide the science-based evidence for inclusive sustainability impact.